2018
DOI: 10.1016/j.ynstr.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Alternations in functional connectivity of amygdalar subregions under acute social stress

Abstract: The amygdala has long been considered a vital region involved in acute and chronic stress responses. Extensive evidences from animal and human studies suggest that the functional connectivity of amygdalar subnuclei (basolateral amygdala (BLA), centromedial amygdala (CMA) and superficial amygdala (SFA)) undergo specific alterations in stress-related psychopathology. However, whether and how intrinsic functional connectivity within the amygdalar subcomponents is differently altered in the aftermath of an acute s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…The interaction between SFA and olfaction has been associated with changes in emotional states 18 . Yet, there is evidence that it interacts with posterior regions associated with visual processes: A study of acute stress and rs-fMRI showed that SFA connectivity with the occipital lobe is stronger relative to the BLA and CMA connectivity with that same lobe 67 . Other studies have identified changes in bilateral SFA activity evoked by facial expressions: the SFA complex selectively captures the social value of the sensory information received 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between SFA and olfaction has been associated with changes in emotional states 18 . Yet, there is evidence that it interacts with posterior regions associated with visual processes: A study of acute stress and rs-fMRI showed that SFA connectivity with the occipital lobe is stronger relative to the BLA and CMA connectivity with that same lobe 67 . Other studies have identified changes in bilateral SFA activity evoked by facial expressions: the SFA complex selectively captures the social value of the sensory information received 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus is believed to be a gateway for primary sensory output to the cerebral cortex and is involved in various cognitive functions, such as attention, consciousness and emotion (J. Chang and Yu, 2018b; Crick and Koch, 2003; Haber and Calzavara, 2009; Shipp, 2004; Ward, 2013). Previous studies found that the thalamus played a part in creating a wide range of emotions, especially negative emotions, and was involved in emotion memory storage through its connection with the hippocampus (Lane et al, 1997; Ward, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Acute social stress has been linked to FC changes between the amygdala and the left putamen, part of the dorsal striatum. This brain region is involved in habitual and automatic behavioral responses; its FC with the amygdala has been shown to increase after stress induction, indicating a shift from a flexible and controlled response to more habitual behavior under stress ( 52 ). The left mediofrontal orbital cortex is part of the social cognitive network, which helps us understand and interact with other people ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%